State Role Model in Regulating Market in Indonesia on Islamic Perspective - Mustapa Khamal Rokan (Ijtimā`iyya: Journal of Muslim Society Research, 2016)
Background of this research is the traditional market alienation due to unbalance compete with modern market on the retail market in Indonesia. Limited capital, business management simple and limited networks make traditional markets are not able to compete with the modern market. This research use qualitative methods and use a case-based approach (statute approach) the Commission’s decision number 09/KPPU-L/2005 and the Commission’s Decision No. 03/ KPPU-LI /2000 and history approach, the history of the market Prophet Muhammad’s time and during the time of the Islamic empire. In addition, this study also helped to pull through direct surveys in several markets in Jakarta and Medan. The result of this research is models of the pressing role state (sadd) by prohibition of monopolistic practices, intervention of price and the location, state role with a capital acces (fath) by empowering, providing capital assistance, as well as collaboration (jam’u) to encourage cooperation between traditional and modern market.